2009
DOI: 10.1097/mpa.0b013e318190d77a
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Intrahepatically Transplanted Islets Labeled With Feridex-Polyethyleneimine Complex Using a Clinical 3.0-T Magnetic Resonance Imaging Scanner

Abstract: Either spot counting or signal intensity measurement provides a perfect quantification of transplanted and surviving islets in vivo. Feridex-PEI provides an effective and safe way to label islets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Undoubtedly, this capability is important for longitudinal MR tracking of transplanted IPCs in the liver. In previous studies 23, 27 , the majority of cells in the core region of isolated islets were not labeled with SPIONs, probably due to the difficulty of dispersing SPIONs into the core of the islets. This low level of core labeling might result in a false sharp decrease in the total areas of hypointense spots on MR images even when only peripheral SPION-labeled islet cells are destroyed.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Undoubtedly, this capability is important for longitudinal MR tracking of transplanted IPCs in the liver. In previous studies 23, 27 , the majority of cells in the core region of isolated islets were not labeled with SPIONs, probably due to the difficulty of dispersing SPIONs into the core of the islets. This low level of core labeling might result in a false sharp decrease in the total areas of hypointense spots on MR images even when only peripheral SPION-labeled islet cells are destroyed.…”
Section: Discussionmentioning
confidence: 82%
“…Several groups have demonstrated the feasibility of imaging pancreatic islets by labeling with SPIONs in mouse, rat and monkey models of T1D 12, 18, 27 . However, few studies have considered the temporal relationship between the loss of SPION-labeled IPCs on MRI and the decrease in blood insulin or C-peptide levels, and few have demonstrated that SPION-based MR tracking is more sensitive for timely detection of IPC loss than measuring blood insulin or C-peptide levels.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Evgenov et al [26], iron distribution within islet cells is not uniform, ranging from 10% to 70%. Recent studies tried to improve efficacy of islet labeling by using liposomes or polyethyleneimine [28,29]. It was shown that isolated human and rodent islets can be labeled with SPIO nanoparticles without impairing their insulin-secreting capacity or viability [24,25,27].…”
Section: Spio Labeling Studiesmentioning
confidence: 99%
“…liposomes >300 nm in diameter) can further hinder uptake and affect islet function and viability. Label uptake can be enhanced using contrast agent with special coatings [68, 69], specific antibodies [70], encapsulation of the agent in specially formulated liposomes [71] or binding to positively-charged peptides loaded by electroporation [72]. Several of these approaches are not easily translatable to the clinic owing to their experimental nature, or financial or logistical difficulties.…”
Section: Mrimentioning
confidence: 99%